Systems thinking in systems engineering - Camelia, Fanny; Ferris, Timothy L. J. (Wiley, 2016)
Systems thinking (ST) offers a holistic approach rather than a reductionist approach, through appreciating all the interrelated dimensions of complex problems. It is important for understanding and interacting with all kinds of systems, in order to manage complex problems. However, the broad range of the ST‐related literature found in various disciplines, generates a great deal of disagreement about definitions and understanding of systems thinking. Despite the current ambiguities of ST definitions, its underlying philosophy has a long history. This paper aims to clarify what ST is in the modern day and why it is defined in so many different ways. It identifies a number of interpretations of systems thinking with the purpose of clarifying what it is and why it is variously understood. The main aims of this paper is to propose a new ST construct, and to define its role in the practice of Systems Engineering (SE). This paper then draws implications of the new ST construct for SE education.